Effect of lactose hydrolysis and salt content on the physicochemical, microbiological, and sensory properties of ayran. (June 2022) - Kocabaş, Handan; Ergin, Firuze; Aktar, Tugba; Küçükçetin, Ahmet
Abstract: Ayran is a salty drinkable yoghurt, but lactose in ayran induces lactose intolerance. This can be overcome by production of lactose-free or lactose-reduced ayran. Milk with 50% and 100% lactose hydrolysis by β-galactosidase was therefore used for alternative lactose-reduced or lactose-free ayran production. Physicochemical, microbiological, and sensory analyses were performed during storage at 4 °C for 28 days. Syneresis and flow behaviour index values increased, and apparent viscosity and consistency coefficient values decreased with increasing lactose hydrolysis level, salt content (0.5 and 1%), and storage period. No significant effects of lactose hydrolysis level and salt content on the counts of Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus were found, while counts of these bacteria decreased during the storage period. Sensory evaluation highlighted that the 1% salt-containing ayran samples, which had higher scores of overall liking than 0.5% salt-containing ones, were significantly different from commercial ayran within the storage period.